2006
DOI: 10.1007/s10562-006-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene and Ethylene Hydrogenation on Alumina Supported Pd-Ag Model Catalysts

Abstract: Adsorption and co-adsorption of ethylene, acetylene and hydrogen on Pd-Ag particles, supported on thin alumina films, have been studied by temperature programmed desorption (TPD). The TPD results show that adding of Ag to Pd suppresses overall hydrogenat ion activity but increases selectivity towards ethylene, i.e. similar to that observed on real catalysts. The results are rationalized on the basis of a complex interplay between surface and subsurface hydrogen species available in the system, whereby the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
185
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(201 citation statements)
references
References 28 publications
7
185
0
9
Order By: Relevance
“…The hydrogenation pathway from acetylene to ethylene and further to ethane (reactions 1-3) does not require assemblies of active sites in contrast to the oligomerisation reaction (4) leading to higher hydrocarbons [15,42,43]. Higher hydrocarbons can be dehydrogenated to form carbon deposits and, thus, deactivate the catalyst [44][45][46][47][48][49].…”
Section: Increased Selectivity and Stability Of Pdga And Pd 3 Gamentioning
confidence: 99%
“…The hydrogenation pathway from acetylene to ethylene and further to ethane (reactions 1-3) does not require assemblies of active sites in contrast to the oligomerisation reaction (4) leading to higher hydrocarbons [15,42,43]. Higher hydrocarbons can be dehydrogenated to form carbon deposits and, thus, deactivate the catalyst [44][45][46][47][48][49].…”
Section: Increased Selectivity and Stability Of Pdga And Pd 3 Gamentioning
confidence: 99%
“…The hydride has higher mobility than the surface hydrogen and can hydrogenate surface adsorbates upon emerging to the surface [3]. Thus, the amount of bulk-dissolved hydrogen seriously affects the activity and selectivity of structure-sensitive hydrogenation reactions [4].…”
Section: Introductionmentioning
confidence: 99%
“…The hydride has higher mobility than the surface hydrogen and can hydrogenate surface adsorbates upon emerging to the surface [3]. Thus, the amount of bulk-dissolved hydrogen seriously affects the activity and selectivity of structure-sensitive hydrogenation reactions [4].Geometrical and electronic information of palladium nano-particles and of palladium hydride can be obtained from X-ray absorption spectroscopy (XAS) at the K and L edges [5,6]. At the Pd K edge XAS, the formation of palladium hydrides was generally deduced from an increased interatomic distance in EXAFS analysis [5].…”
mentioning
confidence: 99%
“…Some Pd facets (e.g., 111) are not prone to carbon dissolution, so hydrogen dissolved in the nanoparticle leads to unselective full hydrogenation. Temperature-programmed desorption (TPD) studies have confirmed that sub-surface hydrogen species lead to non-selective hydrogenation, while surface ones selectively hydrogenate alkynes to alkenes [32]. In addition, according to DFT calculations, the carbide phase affects reaction energeticsonly surface hydrogen adsorption is exothermic, but bulk hydrogen dissolution is suppressed in the presence of Pd-C [33].…”
Section: Figurementioning
confidence: 99%
“…These catalysts produced no alkanes at all, but, instead, significant amounts (up to 70%) of undesired oligomers were formed. Ota et al [25] compared Pd [39,40]. The intermetallic catalyst showed a selectivity of 70% as opposed to 20% for Pd catalyst.…”
Section: Gas-phase Hydrogenationmentioning
confidence: 99%